The algorithmic mirror: can authentic narrative selfhood persist in an AI-mediated world? - Cao, Yuting (Nanyang Technological University, 2025)
This paper examines how AI-assisted social media platforms shape the formation of narrative identity. Drawing on Schechtman’s theory of narrative selfhood and the Extended Mind Thesis (EMT), I argue that these platforms do not merely support self-expression but function as cognitive systems that retrieve and frame identity-related content in ways that qualify as cognitive extensions. However, this extension introduces structural constraints that affect authenticity.